LEADERSHIP INTELLIGENCE OF GUIDANCE AND COUNSELING STUDENTS BASED ON ACEH, GAYO, AND KLUET TRIBES - Yulizar, Yulizar; Fajriani, Fajriani (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2022)
This study aims to obtain an overview of the leadership intelligence of Guidance and Counseling students based on their ethnic backgrounds in the province of Aceh, namely Aceh, Gayo, and Kluet tribes. This research employed a quantitative research approach. Data was collected through the Leadership Intelligence Questionnaire (LIQ) instrument developed by Ronthy. The research population was all students in Guidance and Counseling in the even semester of 2020/2021, totaling 343 students. By using the Slovin formula, the research sample amounted to 185 people. The research data used descriptive analysis. Thus, it can provide an overview of the leadership intelligence profile of student groups in each ethnic group which can be the basis for developing personal services and as a reference in research development related to socio-cultural-based guidance and counseling.